Analysis of Consumer Behavioral Factors Between Online Shopping and Physical Store Experience in the M-Commerce Era - Ovidiu-Aurel Ghiuță; Andreea Nistor (Telecom)
Consumer behavior has changed considerably over time. In recent decades, people have used resources at a rate that exceeds the total consumed throughout history. This paper aims to address the determinants of the smartphone purchase decision, emphasizing gender differences, price influence, and previous online shopping experience. The methodology used combines a bibliometric review of the literature to identify major trends in consumer behavior research and a quantitative research survey that provides insight into consumer behavior in the smartphone purchase process. The survey highlights brand preferences, purchase patterns, product selection criteria, and the influence of socioeconomic factors on the purchase decision, identifying the determinants of online versus physical store purchase decisions among young consumers in the northeastern, east, and southeastern regions of Romania. Thus, our analysis aims to identify the variables influencing consumer preferences and to assess the statistical significance of these differences using quantitative methods and relevant statistical tests. The collected data came from a valid sample of 456 respondents for the general analysis and 271 valid cases for the online shopping analysis. The analysis shows that gender is a significant predictor of online purchase decisions, with men being 2.65 times more likely to purchase a smartphone online than women. The collected data were analyzed using t-tests, Chi-square tests, and logistic regression to assess the influence of variables on online smartphone purchase intention.